A Non-Iterative Network Utilization Pricing Mechanism for P2P Energy Trading - Yun Liu; Yunqiang Gao; Yuanzheng Li; Jizhong Zhu; Hoay Beng Gooi (CSEE Journal of Power and Energy Systems, 2024)
To sustain operation and maintenance of an active distribution network (ADN), a network fee should be charged by the distribution network service provider (DNSP) for facilitating the P2P energy trading service. To this end, this paper models the interaction among the DNSP and multiple prosumers as a Stackelberg game, and then develops a non-iterative and decentralized transactive mechanism to simultaneously achieve optimal network utilization pricing and peer-to-peer (P2P) trading. Simulation results in an ADN with four prosumers connected to a common substation bus validate the effectiveness and efficiency of the proposed scheme.